A história (de)codificada: prolegômenos para uma hermenêutica digital - Santos, Murilo Gonçalves dos (2022)
Faced with the global context of digitization of human culture and cultural production, this thesis aims to present the fundamental traits of a digital historical hermeneutics. For this, we start from the construction of the problem from the hypothesis that digitalization has definitively altered the ontological and epistemological foundations of historical science, which gives rise to a new set of conditions for the possibility of knowledge. In the digital age, history must renew its status as a science of interpretation. One of the clear signs of this need is the recurrence of the use of the term “crisis” in the general discourse, and, for this reason, it will be a matter of examining the history of the historical discipline as the history of its successive crises, in order to understand in what sense the issue of digitization justifies this use. In a second moment, the modern hermeneutic paradigm is examined based on its presence in historical reflection and, later, on its elevation to the philosophical status of ontology. The assumptions of the hermeneutic paradigm are confronted with reflections on media theories in order to show how interpretation is a process mediated and determined by available technologies. Finally, the possibility of a digital hermeneutic is presented from reflections on digitized culture and on the engagement of history and human sciences with digital technologies. These reflections point to the inevitability of ontological considerations: both about the character of the digital, thought of as a code, and about the programming languages that give logical form to the code. In the end, digital hermeneutics proves to be viable by maintaining a dialectic between the technical-ontological aspects and the aspects of the culture in which they are manifested.